Medium and large-scale farmers and agricultural mechanization in Ghana: Survey results - Chapoto, Antony; Houssou, Nazaire; Mabiso, Athur; Cossar, Frances (International Food Policy Research Institute, 2014)
IFPRI’s Ghana Strategy Support Program has tackled a diverse research agenda on Ghana’s agriculture and economic development. This survey was planned and executed in order to address key policy and research questions which have arisen as priorities for the research agenda, but for which there has been a lingering data gap. Successful commercialization of farming enterprises and farmer entrepreneurship are thought to embody the key features of structural transformation and provide a pathway out of poverty and subsistence agriculture for the rural farm households. The past decade has seen several African countries increase their agricultural growth, largely driven by increases in land area cultivated instead of productivity increases. The debate on whether Africa should pursue a strategy of agricultural transformation through large-scale or smallholder farming rages, with little attention to a special group of smallholder farmers that have transitioned to become medium- and large-scale farmers. In Ghana, we have seen the government and some development agencies begin to design agricultural development programs centered on homegrown large-scale farmers and other commercial entities as nucleus change agents to help create a vibrant and more commercialized smallholder sector. For example, the government has been implementing the block farm program as well as procurement and sale of machinery at subsidized prices to medium and large-scale farmers. On the other hand, through the financial support of USAID, the Agricultural Development and Value Chain Enhancement (ADVANCE) Project uses the value chain approach to help link smallholder farmers to markets, finance, inputs and equipment services and information through relatively larger nucleus (commercial) farmers and large traders (aggregators) who have the capacity to invest in the value chain. Essentially these models are based on the premise that there exist symbiotic relationships between the small-scale farmers and the larger farmers and that there are positive spillover effects from developing or channeling assistance to these nucleus farmers. If indeed smallholder farmers can benefit from the existence of large-scale and medium farmers in their communities then there is need to recast the debate and focus on finding ways to leverage these interactions in order to transform Ghana’s agricultural sector.